2020
DOI: 10.1080/1343943x.2020.1742582
|View full text |Cite
|
Sign up to set email alerts
|

Yield and related traits for a soybean breeding line ‘Tokei 1122’ with QTLs for long terminal racemes under high planting density conditions

Abstract: Low-branching soybean cultivars have few nodes per plant, and there have been many cases in northern Japan where growing these cultivars at high plant densities did not improve yield. Soybean cultivar 'Tokei 1122ʹ (T22), which has a long terminal raceme, was bred to improve the yield of low-branching cultivars under dense planting conditions. To elucidate the effects of long racemes on the suitability of T22 for dense planting, we compared the yield and yield components of T22 and 'Toyoharuka' (TH), which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Lodging was one of the important factors for the reduction of soybean yield and quality; studies have found that lodging causes soybean yield reduction up to 20-30% and up to 50% in severe cases [16,17]. Lodging mostly occurred in the internodes of soybean stem; therefore, the pros and cons of stem base traits were closely related to the lodging resistance of the plant [18][19][20]. An important indicator for measuring the degree of lodging resistance of soybean stems was the stem lodging resistance index associated with stem base resistance, stem thickness, and above ground fresh and dry biomass [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Lodging was one of the important factors for the reduction of soybean yield and quality; studies have found that lodging causes soybean yield reduction up to 20-30% and up to 50% in severe cases [16,17]. Lodging mostly occurred in the internodes of soybean stem; therefore, the pros and cons of stem base traits were closely related to the lodging resistance of the plant [18][19][20]. An important indicator for measuring the degree of lodging resistance of soybean stems was the stem lodging resistance index associated with stem base resistance, stem thickness, and above ground fresh and dry biomass [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This is an effective way to investigate the potential mechanisms of inflorescence development to improve the seed yield of plants and crops [ 3 , 4 , 5 ]. Many small flowers emerge on the inflorescence peduncle, and the elongation capacity of the inflorescence peduncle affects raceme length and eventually influences flower and seed development [ 6 ]. Alfalfa ( Medicago sativa ) is an important forage, food, and Chinese herbal medicine planted worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%